Pengaruh Pijat Aromaterapi Lavender Terhadap Tingkat Nyeri Persalinan Kala I Fase Aktif - Finta Isti Kundarti; Ira Titisari; Naning Tri Windarti (Akademi Keperawatan Dharma Husada Kediri, 2014)
Pain in the labor are predisposition for anxiety, hyperventilation, thus causing oxygen requirements and increased blood pressure. Pain in the labor can be reduced by non- pharmacological methods, one of which is using aromatherapy. Lavender as an aromatherapy effect relaxation, pain relief, reduces anxiety and causes calmness. The purpose of this research was to know the effect of lavender massage aromatherapy to the level of the first stage of labor pain in the active phase of first stage labor. The research design used quasi experiment with pre-test post-test with control group design. The population in this research that the whole maternal active phase of the first stage in BPM Blabak’s Community Health Center Kediri Regency. The research time is June 23 until July 19 sampling techniques. The research instrument used scale observation. Statistical tests in this study using the paired t test.The results showed t value (11,000) > t table (2,262) and P value (0.000) < α (0.05), then H0 is rejected, which means there is effect of lavender (Lavandula angustifolia) massage aromatherapy to the pain labor level of the active phase in the first stage of labor. So the conclusion of lavender massage aromatherapy down the level of pain in the active phase of the first stage of labor. This method can be applied midwives to help reduce pain during childbirth. Keywords: Lavender Aromatherapy, Pain, Labor, Massage